Network Broadcasting System (NBS): Implementation and Its Obstacles - Amin Shabana (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
The draft revision of Law No.32/2002 on broadcasting currently has entered the stage of legislation body of DPR RI  (Baleg).  The  revision  eliminated  the  obligation  of  the  Network  Broadcasting  System  (NBS)  for  Private Broadcasting  Institutions  (LPS)  considered  have  neglected  the  public  interest  of  the  broadcasting  sector.  For many  groups,  especially  civil  society,  this  new  policy  regarding  SSJ  is  a  step  backward.  The  decentralization spirit of the broadcasting industry is threatened to be continued. While the implementation of the NBS itself has been carried out half-heartedly. The purpose of this study is to know the implementation of NBS carried out by the LPS designated as the central stations and the obstacles faced in managing the implementation of NBS with network stations located in the region. The theory used in this study are broadcasting, mass media and NBS. This study uses a qualitative approach with descriptive method. Data collection techniques: interview with the Central Indonesian Broadcasting Commission, study literature, and documentation; The validity test of the data is through informant  triangulation  to  organization  that  conduct  broadcast  advocacy,  Remotivi.  The  results  of  this  study indicate  that  NBS  implementation  is  still  not  running  optimally.  LPS  still  has  a  reluctance  in  preparing infrastructure facilities to implement NBS. Meanwhile the impact of NBS at the local level is also increasingly complex in various sectors of life. Various obstacles start from regulation, political will of all NBS stakeholders and weak supervision caused NBS still far from expectations. This situation makes the centralistic broadcasting system remain dominant. Keyword: Decentralization, Broadcasting Industry, Network Broadcasting Systems